(untitled) (Journal of the College of Basic Education, 2022)
Toxoplasmosis is an endemic infectious disease, very widely distributed in all parts of the world and called a disease of the five continents and depending on the geographical location since 15% to 85% of the human population asympmatically infected. The present study was carried out on total number one hundred and thirty three women suspected of having toxoplasmosis with and without abortion. The titers of serum immunoglobulin M and G (IgM and IgG) of anti- Toxoplasma antibodies were detected by enzyme linked immunosorbent assay (ELISA) according to the final diagnosis of toxoplasmosis. It was found that women with toxoplasmosis had higher levels of median values of IgM and IgG Abs of T.gondii that were 0.420 ± 0.035and 5.461 ± 0.39respectively, while women that did not have toxoplasmosis, had 0.381 and 0.8 respectively . Serum levels of IL-18 and IL-5 detected by ELISA were 87.01 ± 10.02pg/ml and 805.70 ± 122.30pg/ml respectively in women with toxoplasmosis , while in women that did not have toxoplasmosis the levels were 67.59 ± 10.21pg/ml and 126.62 ± 35.96pg/ml respectively